The effect of climate on the physical and physiological characteristics of cotton seeds after delinting - Elham Faghani; Shahram Nowrouzieh; Ghorban Ali Roshani (علوم و فناوری بذر ایران)
The seeds harvested from different climates in the process of seed delinting in the factory had different vigor and emergence in the field. Therefore, this research was carried out with the aim of investigating the physiological and mechanical characteristics of delinted seeds in the factory. This project was done as a completely randomized block. The blocks were cultivars from different climate. Finally, traits such as the percentage of mature and immature seeds, seed coat and endosperm weight, ion leakage, seed scratchiness, density, volume, and breaking force of seed were studied. The results showed that the percentage of immature seeds was the highest in Golestan in dry-hot and Khordad in dry-cold. The highest percentage of scratched seeds was in Golestan in dry-moderate and the lowest percentage of scratched seeds was in Golestan in dry-hot province, Kashmer in dry-cold climate and Latif in dry-moderate. The highest percentage of healthy seeds that completed their physiological maturity was observed in Latif in dry-moderate with 98.8%. While the Golestan in the dry-hot had the lowest percentage of mature seed weight among the studied cultivars. The highest and the lowest failure force were in Khurshid, 83.75 N, and Golestan from dry- hot regions with 47.9N. In general, results cleared that failure force, percentage of crashed,,, broken, immature,, 100-seed weight and seed size for Golestan in both climates dry-moderate and dry-hot showed that both hull seed and de-hulled the Golestan seeds which are produced in dry-moderate are more tolerant rather than the seeds of dry-hot.